Respirable indium exposures, plasma indium, and respiratory health among indium‐tin oxide (ITO) workers. Issue 7 (24th May 2016) - Cummings, Kristin J.; Virji, M. Abbas; Park, Ji Young; Stanton, Marcia L.; Edwards, Nicole T.; Trapnell, Bruce C.; Carey, Brenna; Stefaniak, Aleksandr B.; Kreiss, Kathleen
Abstract : Background: Workers manufacturing indium‐tin oxide (ITO) are at risk of elevated indium concentration in blood and indium lung disease, but relationships between respirable indium exposures and biomarkers of exposure and disease are unknown. Methods: For 87 (93%) current ITO workers, we determined correlations between respirable and plasma indium and evaluated associations between exposures and health outcomes. Results: Current respirable indium exposure ranged from 0.4 to 108 μg/m 3 and cumulative respirable indium exposure from 0.4 to 923 μg‐yr/m 3 . Plasma indium better correlated with cumulative (rs = 0.77) than current exposure (rs = 0.54) overall and with tenure ≥1.9 years. Higher cumulative respirable indium exposures were associated with more dyspnea, lower spirometric parameters, and higher serum biomarkers of lung disease (KL‐6 and SP‐D), with significant effects starting at 22 μg‐yr/m 3, reached by 46% of participants. Conclusions: Plasma indium concentration reflected cumulative respirable indium exposure, which was associated with clinical, functional, and serum biomarkers of lung disease. Am. J. Ind. Med. 59:522–531, 2016. Published 2016. This article is a U.S. Government work and is in the public domain in the USA.